ANALISIS PENDAPATAN USAHATANI PEPAYA CALIFORNIA (Carica papaya L) DI DESA BATI-BATI KECAMATAN BATI-BATI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Wasdiyanta; Mahdalena, Zulipah; Ramadhana, Sri (Fakultas Pertanian UVAYA Banjarmasin, 2024)
The aim of this research is technically to find out how to cultivate papaya plants and financially to find out the costs, receipts and income from papaya farming in Bati-Bati Village, Bati-Bati District. The research method used is a case study. The research results showed that the amount of explicit costs consisting of input costs, labor outside the family, rental costs and depreciation was IDR 53,460,416. Total receipts amounted to Rp. 216,000,000,- and total income of IDR 162,539,584